Socializing the Addition of Jambal Siam (Pangasius hypophtalmus) Fish Stomach Oil and Kerapu (Cromileptes sp) Fish Oil in Baby Porridge for Satisfy Omega 3 and Omega 6 Standard - Mirna Ilza; Yusni Ikhawan Siregar (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
The research aim on the socialization of the addition of jambal siam (Pangasius hypophtalmus)fish stomach oil and kerapu (Cromileptes sp) fish oil in baby porridge for satisfy omega 3 and omega6 standard was implemented around Pekanbaru and Bangkinang (Kampar district). The additionof fish oil is done based on the standard of the WHO weight which conform to the age of the baby.The baby’s weight is very less than WHO standard dose given 50 mg/day, less weight given 40 mg/day, and normal weight is 30 mg/day. Weight gain weighed and also observed the developmentof psychomotor babies each week for 8 weeks. Based on initial weight babies at the age of 10–12months without the addition of jambal siam (Pangasius hypophtalmus) fish stomach oil and kerapu(Cromileptes sp) fish oil in baby porridge, 70.7% had a normal body weight increase and 23.3%have added weight which is too late. After the addition of jambal siam (Pangasius hypophtalmus)fish stomach oil and kerapu (Cromileptes sp) fish oil in baby porridge obtained added weight andmotor development towards a better i.e. were 93.4% had normal motor development of appropriateage and the remaining 6.6% still have weight and psychomotor development too late i.e. newbornweight was initially very less than the WHO standard.Keywords: Fish oil, baby, body weight, physichomotor